Behavioral intention towards American fast food restaurants among Malaysian consumers - Chong, Chi Qing; Kok, Beng Kee (2019)
The objective of executing this research project is to investigate the factors of food quality, service quality and restaurant environment that affected customer satisfaction and behavioral intention towards American fast food restaurants among Malaysian consumers. To achieve the goal of this research project, research questions, and four hypotheses are formed and examined. Furthermore, each hypothesis is measured and outcomes generated are afterward explained. Besides that, literature reviews are given in this research project to gain an insight into the influential elements on dining experience of consumers and to provide the justification towards the research questions and problems. Primary data are gathered via survey questionnaire for these research objectives and 200 sets of questionnaire were distributed to the target interviewees who are live in Klang Valley. By utilizing Statistical Package for Social Science (SPSS), data gathered via survey questionnaires are able to be analyzed, and outcomes obtained are in the table form and charts. Moreover, main findings of this research project are discussed in order to better understand the relationship between food quality, service quality, and restaurant environment towards customer satisfaction as well as the relationship between customer satisfaction and behavioral intention. After completing the research, we acknowledged that all of these elements are significant in affecting customer satisfaction, which later customer satisfaction will affect the behavioral intention towards American fast food restaurants among Malaysian consumers. On the other hand, managerial implications have been discussed to provide useful information and in-depth analysis to the American fast food restaurateurs. Finally, the limitations confronted in this research will be addressed and recommendations will be formulated to assist the future researchers in managing these addressed limitations.